The Impact of Facial Lipofilling on Patient-Perceived Improvement in Facial Appearance and Quality of Life - Tepavcevic, Brankica; Radak, Djordje; Jovanovic, Milan; Radak, Sandra; Tepavcevic, Darija Kisic (Facial Plastic Surgery, 2016)
An investigation of the effect of facial lipofilling on patient's satisfaction is a challenging and ongoing research area. Therefore, the aim of this study was to investigate the impact of aesthetic intervention on self-perceived improvement in facial appearance and quality of life (QoL) after 1- and 6-month follow-ups. In the period from October 1, 2014, to March 1, 2015, a total of 63 consecutive subjects who underwent a facial lipofilling were included in the study. The satisfaction with facial appearance was estimated by using the Satisfaction with Facial Appearance Overall scale. QoL was assessed by using the 36-Item Short Form Health Survey (SF-36). Severity of depressive and anxiety symptoms was quantified by using the Hamilton depression and anxiety rating scales. The self-esteem was assessed by Rosenberg self-esteem scale. The average Satisfaction with Facial Appearance Overall scale score at baseline was 45.5 ± 13.0, while this score reached values of 84.5 ± 16.2 after 1 month (Z = −6.744, p < 0.001) and 82.7 ± 12.6 after 6 months (Z = −6.545, p < 0.001) of follow-up. The mean change of Satisfaction with Facial Appearance Overall scale score from baseline to 1-month follow-up was 38.9 ± 21.2 and from baseline to 6-month follow-up was 37.1 ± 18.9. Statistically significant improvement in QoL at each subsequent time point, compared with those at baseline, was detected for all domains of the SF-36 except for subscales of physical functioning and pain. It has been highlighted that advanced social life was strongly associated with improvement in satisfaction with facial appearance, better self-esteem, and lower level of anxiety and depression during the period of follow-up after facial lipofilling. The results of this study supported the hypothesis that the level of self-confidence and mental health–related QoL could be significantly improved following facial lipofilling treatment.
Keywords: lipofilling; facial appearance; self-esteem; quality of life; follow-up